Numerical Investigation of the Influences of Wellbore Flow on Compressed Air Energy Storage in Aquifers - Yi Li; Keni Zhang; Litang Hu; Jinsheng Wang (Geofluids)
With the blossoming of intermittent energy, compressed air energy storage (CAES) has attracted much attention as a potential large-scale energy storage technology. Compared with caverns as storage vessels, compressed air energy storage in aquifers (CAESA) has the advantages of wide availability and lower costs. The wellbore can play an important role as the energy transfer mechanism between the surroundings and the air in CAESA system. In this paper, we investigated the influences of the well screen length on CAESA system performance using an integrated wellbore-reservoir simulator (T2WELL/EOS3). The results showed that the well screen length can affect the distribution of the initial gas bubble and that a system with a fully penetrating wellbore can obtain acceptably stable pressurized air and better energy efficiencies. Subsequently, we investigated the impact of the energy storage scale and the target aquifer depth on the performance of a CAESA system using a fully penetrating wellbore. The simulation results demonstrated that larger energy storage scales exhibit better performances of CAESA systems. In addition, deeper target aquifer systems, which could decrease the energy loss by larger storage density and higher temperature in surrounding formation, can obtain better energy efficiencies.